TINJAUAN HUKUM PIDANA ISLAM PASAL 412 UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KOHABITASI - Ritonga, Rahul Sani; Mukhsin, Abd. (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research examines the regulation of cohabitation in Section 412 of Law No. 1 of 2023 and compares it with adultery sanctions in Islamic criminal law. The background of the problem raised is that Article 412 provides leniency for adultery offenders compared to Article 411 which regulates adultery, where the punishment for cohabitation offenders is lighter and the proof process uses an absolute complaint offense. This study employs normative legal techniques. with descriptive data analysis techniques. The results The discussion shows that in the review of Islamic criminal law, cohabitation offenders are considered equivalent to adultery offenders. In Islam, cohabitation is an extension of the crime of adultery so that the criminal sanctions are equalized, both for muá¸¥á¹£an (married) and ghairu muá¸¥á¹£an (unmarried). The perpetrator of cohabitation is subject to The perpetrators of cohabitation are subject to 100 lashes or stoning according to the category of adultery. The study's findings indicates that the regulation of cohabitation in Article 412 of Law Number 1 Year 2023 has significant differences with Islamic criminal law. Article 412 provides a lower penalty than Article 411 on adultery, in contrast to Islamic criminal law which equates criminal sanctions for cohabitation offenders with adultery offenders, namely 100 lashes or stoning according to the type, whether the category of zina muá¸¥á¹£an or ghairu muá¸¥á¹£an.